Therapeutic Communication Process of Counselors in Psychological Assistance (Study on Domestic Violence Victims at Damar Association) - Salsabilla, Syaira; Verawati, Noning; Pienrasmi, Hanindyalaila (Universitas Dharmawangsa Medan, 2025)
This study aims to describe the therapeutic communication process employed by counselors in providing psychological assistance to domestic violence survivors at Damar Association, Lampung. Therapeutic communication serves as a crucial aspect in helping survivors cope with trauma and rebuild their sense of safety and self-confidence. This research employs a qualitative approach within the constructivist paradigm. Data were collected through in-depth interviews and observations involving counselors, advocacy staff, and survivors who had received assistance. The results indicate that counselors implement therapeutic communication through four key phases: pre-interaction, orientation, working, and termination. Techniques utilized include active listening, clarification, reflection, information sharing, and supportive non-verbal communication. The success of therapeutic communication is also influenced by the presence of support systems from the survivor's family and social environment. This study contributes to the development of therapeutic communication practices within NGOs assisting domestic violence survivors and emphasizes the importance of empathy, warmth, and interpersonal communication skills in the psychological recovery process.